In Vitro Activity of Propolis on Oral Microorganisms and Biofilms - Alexandra Stähli; Hannah Schröter; Simonetta Bullitta; Francesca Serralutzu; Antonio Dore; Sandor Nietzsche; Egle Milia; Anton Sculean; Sigrun Eick (MDPI AG, 2021)
Natural products are being discussed as alternatives to commonly used chemicals in antimicrobial therapy. The study aimed to investigate the antimicrobial activity of propolis against microbial species associated with caries, periodontal disease, and Candida infections. Two commercially available ethanolic extracts of Brazilian and one of European propolis (EEP) were used. The minimal inhibitory concentrations (MIC) of propolis and controls against eight microbial strains were determined. Scanning and transmission electron microscopy (SEM and TEM) images visualized the effect of propolis on microorganisms. Subsequently, the activity on three different multi-species biofilms (both formation and existing biofilms) was assessed. All MIC values of the Brazilian EEPs were low against the tested oral species (≤0.1 mg/mL-3.13 mg/mL propolis (Candida albicans)). The European EEP had slightly higher MICs than the Brazilian EEPs. The SEM and TEM images suggest an interaction of propolis with the microbial cell wall. The European EEP exhibited the strongest effect on retarding biofilm formation, whereas the Brazilian EEPs were highly active against preformed biofilms (100 mg/mL propolis of both EEPs reduced colony forming unit counts always by more than 6 log10). The antimicrobial and anti-biofilm activities point to the potential of propolis as an adjunct in oral health care products.